Profil Kesadaran Metakognitif Siswa SMA - Gregory Yehezkiel Marhaendra; Natalia Rosa Keliat; Marisa Christina Tapilouw (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
Metacognition is thinking skill about thinking. Metacognitive awareness plays an important role in achieving success of the learning process. The aim of this research was to determine the metacognitive awareness profile of X class high school students in Salatiga. This research was used descriptive quantitative with the technique of determining the subject by purposive sampling. Data collection was carried out in a survey with the Metacognitive Awareness Inventory (MAI) instrument by applying a Likert scale. Based on the results of the research, the knowledge dimension with indicator for declarative knowledge was 72.62%, procedural knowledge was 72.13%, and conditional knowledge was 75.98%. Regulatory dimensions such as; planning indicators reached 74.19%, information management strategies only 64.44%, comprehension monitoring 72.01%, debugging strategies 72.87%, and evaluation 74.90%. The average percentage of metacognitive awareness of X class high school students in Salatiga for each indicator is 72.91%. Based on the results of the study, it was concluded here were several metacognitive awareness survey results whose percentages were below 50%.